Precautionary measures in dealing with Covid-19 pandemic: learning from the Prophet’s tradition - Ali, Mohammed Farid; Abdul Rahman, Shukran; Subhani, Zulqernain Haider (The Companion, 2020)
The world is struck by Novel Coronavirus or COVID-19, an infectious condition that can spread directly or indirectly from one person to another. The virus has seriously affected various countries and disrupted the normal functions of their people. The virus spreads when the droplets coughed or sneezed from an infected person enter into the eyes, nose and mouth of another person; or contaminate the surface in his or her surrounding, only to infect others to come to contact with the surface. Given Covid-19 is an acute and highly contagious viral disease, transmissible through human interactions, there is a need to put in place judicious interventions to eliminate or slow the outbreak